Emissions of Escherichia coli Carrying Extended-Spectrum β-Lactamase Resistance from Pig Farms to the Surrounding Environment - Lili Gao (International Journal of Environmental Research and Public Health, 2015)
The dissemination of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) from food-producing animals to the surrounding environment has attracted much attention. To determine the emissions of ESBL-producing E. coli from pig farms to the surrounding environment, fecal and environmental samples from six pig farms were collected. In total, 119 ESBL-producing E. coli were isolated from feces, air samples, water, sludge and soil samples. Antibiotic susceptibility testing showed that the ESBL-producing isolates were resistant to multiple antibiotics and isolates of different origin within the same farm showed similar resistance phenotypes. Both CTX-M and TEM ESBL-encoding genes were detected in these isolates. CTX-M-14 and CTX-M-15 were the predominant ESBL genes identified. ESBL producers from feces and environmental samples within the same farm carried similar CTX-M types. The results indicated that the ESBL-producing E. coli carrying multidrug resistance could readily disseminate to the surrounding environment.